Hannibal. - Harris, Thomas, ....- (London : Arrow, 2000)
Seven years have passed since Dr Hannibal Lecter escaped from custody, seven years since FBI Special Agent Clarice Starling interviewed him in a maximum security hospital for the criminally insane. The doctor is still at large, but Starling has never forgotten her encounters with Dr Lecter, and the metallic rasp of his seldom-used voice still sounds in her dreams...
Keywords: Fiction